PENERIMAAN NEGARA BERUPA PAJAK DALAM PERSPEKTIF ISLAM - Delphino, Hilmi (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2022)
The essence of the problem in the journal that the author has made which is entitled state revenue in the form of taxes in an Islamic perspective is to explain how tax bases or from bah as a source of state income in the Koran and also hadith because Islam has required the payment of zakat for those who have fulfilled the provisions or obligations regarding the payment of zakat but there may be a situation where zakat can no longer suffice for state financing at that time, levying from the language of taxes is permissible but of course with some very strict provisions and decided by experts. Doriba or tax is included in a form of muamalah activity in the economic field which functions as a fulfillment of the needs of society and the state to fund common needs because there is no Nash which explicitly regulates tax stone in Islamic law resulting in differences of opinion among regarding the law and status of collection of taxes. This study uses the library research method which seeks various sources through reading. It was found in this journal that taxes in Islam exist such as doribah jizyah kharaj humus ushr.